2016
DOI: 10.1007/s10773-016-3216-3
|View full text |Cite
|
Sign up to set email alerts
|

Gravity-Induced Four-Fermion Contact Interaction Implies Gravitational Intermediate W and Z Type Gauge Bosons

Abstract: Coupling fermions to gravity necessarily leads to a non-renormalizable, gravitational four-fermion contact interaction. In this essay, we argue that augmenting the Einstein-Cartan Lagrangian with suitable kinetic terms quadratic in the gravitational gauge field strengths (torsion and curvature) gives rise to new, massive propagating gravitational degrees of freedom. This is to be seen in close analogy to Fermi's effective four-fermion interaction and its emergent W and Z bosons.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Let us first start with the covariant Lagrangian for a (complex) minimally coupled scalar field in an arbitrary non-Riemannian 9 To be more exact, if we consider fermions, they will contribute as a source of torsion to the connection, and there would arise torsioninduced interactions as explained in [54,55]. However, it has been recently argued that such interactions are beyond current experimental reach [63], and therefore we will neglect torsion in our discussion. 10 Notice that it vanishes up to torsion corrections generated by the fermions.…”
Section: Effective Interactions In Rbg Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us first start with the covariant Lagrangian for a (complex) minimally coupled scalar field in an arbitrary non-Riemannian 9 To be more exact, if we consider fermions, they will contribute as a source of torsion to the connection, and there would arise torsioninduced interactions as explained in [54,55]. However, it has been recently argued that such interactions are beyond current experimental reach [63], and therefore we will neglect torsion in our discussion. 10 Notice that it vanishes up to torsion corrections generated by the fermions.…”
Section: Effective Interactions In Rbg Theoriesmentioning
confidence: 99%
“…Afterwards, it was discovered that one can obtain the same results by constructing the gauge theory of the Poincaré group 4 [55,56]. Some authors tried then to understand what could be the observable consequences of torsion and used them to place experimental constraints to the possible existence of a non-vanishing torsion tensor in different contexts [57][58][59][60][61][62][63]. Despite the effort put in understanding the observable effects of torsion, existence (or lack) of observables related to non-metricity is not yet well understood.…”
Section: Introductionmentioning
confidence: 99%
“…1 The word "torsionon," which rolls off the tongue in Spanish, may be a bit hard to pronounce in English. J. Boos and F. W. Hehl have called these degrees of freedom "gravitational W and Z gauge bosons" [12], while F. W. Hehl had earlier suggested the name "roton" [19]. 2 A more appropriate name would be Lorentz connection.…”
Section: A First-order Formalismmentioning
confidence: 99%
“…The presence of propagating torsion modes in this class of theories has been the subject of much investigation; for a recent assessment, see Refs. [12][13][14][15] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…For recent investigations of the cosmology and astrophysics of Einstein–Cartan theory see [ 37 46 ]. In [ 47 ] it was shown that by enlarging the Einstein? Cartan Lagrangian with suitable kinetic terms quadratic in the gravitational gauge field strengths (torsion and curvature) one can obtain some new, massive propagating gravitational degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%